Effects of fertilization gradient on the production performance and nutritional quality of cultivated grasslands in karst areas - Wang, Yuefeng; Tian, Sihui; Shuai, Honggang; Jin, Baocheng; Zhang, Yaoyao; Wei, Junpeng; Niu, Zijing; Ma, Yifeng; Zhao, Xuechun (Frontiers in Plant Science, 2023)
Optimal fertilization is an important measure for managing artificialcultivated grasslands, and a necessary means for maintaining the nutrient balance, yield, and quality of grassland ecosystems. This study aimed to explore the effects of organic fertilizers on the production performance and nutritional quality of artificialcultivated grasslands in karst areas. Two types of monocultured artificialcultivated grasslands (i.e., Medicago sativa and Dactylis glomerata) were employed as the research objects, and a randomized block design was adopted to investigate the effects of five fertilization gradients on the forage height, coverage, yield, and nutritional quality of the artificialcultivated grasslands. According to the results, the plant height, coverage, and yield of M. sativa first presented an increasing trend, then decreased with increasing fertilization gradient, with a peak at 20-30 t/hm 2 fertilization gradient. The height, coverage, and yield of D. glomerata increased gradually with increase in fertilization gradient, and peaked at 40 t/hm 2 . Meanwhile, the crude protein (CP) and ether extract (EE) contents of both grassland types displayed first presented an increasing trend, then decreased with increasing fertilization gradient, and peaked at 10-30 t/hm 2 fertilization gradient. The neutral detergent fiber (NDF) and acidic detergent fiber (ADF) contents of M. sativa presented "N-shaped" and "M-shaped" change trends with increasing fertilization gradient, while those of D. glomerata showed "V-shaped" and "Mshaped" change trends, reaching minimum values under fertilization gradients of 30 and 20 t/hm 2 , respectively. Year, fertilization, and year × fertilization (Y×F) significantly affected the plant heights, coverages, dry/fresh weight ratios, and yields of M. sativa and D. glomerata. The contribution of coverage to the subordinate function of M. sativa was greatest at a fertilization gradient of 20 t/hm 2 . Meanwhile, the subordinate function values of the height and coverage of D. glomerata increased gradually with increasing fertilization gradient, but the difference in the subordinate function value of height was only 0.09%-0.18% under the fertilization gradient of 20-40 t/hm 2 . Evaluation of forage nutrition revealed 10-30 t/hm 2 and 20-30 t/hm 2 as the optimal organic fertilizer application rates for M. sativa and D. glomerata, respectively.